(untitled) (Conferencea, 2024)
In modern society, the situation is radically changing. The world as a whole is becoming multipolar and multicultural, and the leading trends of the modern stage of society’s development are its informatization, globalization, and the accelerating variability of technology. In this article highlights of universal principles of developing the thinking potential of students.